The association of perceived conflict with sadness for long-term care residents with moderate and severe dementia. (October 2018) - O'Rourke, Hannah M; Fraser, Kimberly D; Duggleby, Wendy; Keating, Norah
Objectives: Research into the lived experiences of long-term care residents with dementia has identified perceived conflict, and its impact on sadness, as priorities for quality of life from the perspectives of people with dementia. However, whether and to what extent perceived conflict and sadness are associated has not been previously tested in this population. This study tested the associations between perceived conflicts with staff, family or friends and co-residents and their experience of sadness, and whether cognitive impairment or functional dependence modified these associations. Methods: The study design was cross-sectional, correlational retrospective. Participants were 5001 residents of 613 long-term care facilities in Ontario, Canada with moderate and severe dementia. Clinical administrative data collected from 2012 to 2013 using the Resident Assessment Instrument 2.0 were used to measure the person's perception of conflicts with family/friends, staff, or co-residents, as well as verbal and non-verbal indicators of sadness. Hypotheses were tested using logistic regression, with cluster correction. Results: Sadness (adjusting for age, sex, family/friend contact, pain, cognitive impairment, and functional dependence) was positively associated with perceived conflicts with family or friends (OR 1.91; 95% CI 1.26–2.88; p  = 0.002) and staff (OR 1.51; 95% CI 1.07–2.13; p  = 0.020). These associations did not differ depending on the level of cognitive impairment or functional dependence. The association between co-resident conflict and sadness was statistically significant for people with moderate (OR 2.02; 95% CI 1.45–2.82; p  < 0.001) but not for those with severe dementia (OR 1.18; 95% CI 0.72–1.91; p  = 0.511). Conclusion: Long-term care residents with dementia who perceive conflict with others require support to maintain high quality relationships, particularly with family and friends. Future research should rigorously assess the modifiability of perceived conflict for people with moderate and severe dementia, and whether interventions to ameliorate perceived conflict result in decreased sadness and improved quality of life.